Implementasi Program Sekolah Penggerak di SMAN 1 Tilatang Kamang - Lazwardi, Lisa; Hendriani, Suswati; Haviz, M.; Trisoni, Ridwal; Fadriati, Fadriati (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
Sekolah Penggerak Program is one of the education recovery steps taken by the government. In the implementation of this program, there are five interventions, namely consultative and asymmetrical assistance, improving school human resources, new paradigm learning, data-based planning and school digitalization. Among the five interventions, new paradigm learning is the main focus of schools. Therefore, the purpose of this study is to describe the implementation of the Sekolah Penggerak Program at SMAN 1 Tilatang Kamang on new paradigm learning which includes differentiated learning, a project to strengthen the profile of Pancasila of the students and the process of grade increment and subject selection in class XI. The type of research conducted is qualitative research with case study method. The place of research at SMAN 1 Tilatang Kamang in May to June 2023 conducted by the researcher as the main instrument of research. The data collected through interview, observation and documentation study techniques. The collected data analyzed with the stages of reduction, representation, and drawing conclusions. Data validity was tested using data source triangulation techniques. The results revealed that the school implements Sekolah Penggerak program by focusing on new paradigm learning, namely the implementation of differentiated learning, the project of strengthening sutedents’ profile of Pancasila and conducting the grade increment process as well as the selection of subjects that apply the principles of child-centered learning. Differentiated learning is implemented with three strategies: content differentiation, process differentiation and product differentiation. The determination of differentiated learning strategies is based on data mapping children's learning readiness obtained from diagnostic assessments. The Strengthening Profile of Pancasila Project of Students is implemented with a one-day project scheduling system every week. The process of implementation the project from preparation to assessment is designed based on the themes and profile dimensions set by the facilitation team. The grade increment system from grade X in phase E to grade XI in phase F is based on the achievement of learning objectives and the completion of the project theme in that grade. The selection of elective subjects in grade XI is based on the child's talents, interests, and readiness then the selection process is carried out freely and refers to the results of the child's diagnostic test. Children are given the opportunity to change their elective subjects in the first semester of grade XI by considering the child's learning progress and psychological condition.